Investigation of the problem behaviors emerging in children during the COVID-19 pandemic in Turkey - Sancili, Semanur; Tugluk, Mehmet Nur (Southeast Asia Early Childhood Journal, 2021)
This study aimed to evaluate the effect of the COVID-19 pandemic on the problem behaviors of children within the framework of parental opinions. The study was conducted using case study design, one of the qualitative research methods. The study group was selected based on the criterion sampling method, one of the purposive sampling methods.  The study group of this research consists of 20 Turkish parents with children between 4 and 6 years of age living in the province of Istanbul in Turkey. The analysis of parental opinions revealed that some favorable and unfavorable changes occurred in the children’s playing, sleeping, eating, and hygiene habits during the COVID-19 pandemic. Emotional problems such as boredom, fear, anxiety, irritability, and impatience were found to be more common in children compared to the pre-pandemic period, together with behavioral problems such as non-obedience, desire to attract attention, aggression, hyperactivity, conflicts between siblings. According to the results, COVID-19 pandemic has not only physical but also psychological effects. This study emphasizes the importance of supporting and helping families in the psychological well-being of children during social isolation.